Charge freezing and surface anisotropy on magnetite (100) - COEY, JOHN; SHVETS, IGOR (My University, 1993)
Scanning tunneling microscope images of the (100) surface of slightly nonstoichiometric magnetite taken at room temperature show static arrays of pairs of Fe2+ ions with short?range order, and a charge fluctuation time greater than 103 s. The surface appears to be a Wigner glass with electron pairs localized on adjacent ions as the basic unit. The explanation of Wigner localization at room temperature on the surface only is that the spin?polarized minority?spin band derived from dyz orbitals is stabilized and narrowed by the absence of an apicial oxygen from the B?site octahedron. This leads to surface anisotropy where the Fe2+ spins are pinned normal to the {100} surfaces. Surface anisotropy is expected to outweigh bulk anisotropy in submicron particles.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; Scanning tunneling microscope; Surface magnetism